The Effect of Regional Financial Supervision, Accountability and Transparency of Regional Financial Management on Local Government Performance - Vincentia Wahju Widajatun; Francisca Kristiastuti (Budapest International Research and Critics University, 2020)
This study aims to determine the effect of regional financial supervision on local government performance, the effect of regional financial management accountability on regional government performance, to determine the effect of transparency in regional financial management on regional government performance, and the effect of regional financial supervision, accountability and transparency of regional financial management on performance. Regional government. This research was conducted in West Bandung Regency. The sampling technique used non-probability sampling techniques so that the samples in this study were 34 people. The type of data used in this research is quantitative and qualitative data, while the data source is the primary data source. The method of data collection is done by using a questionnaire. The data analysis technique used multiple linear regression analysis with the help of the SPSS 24.0 program. The results of this study indicate that simultaneously regional financial supervision, accountability and financial management transparency have a significant effect on the performance of local governments. Regional Financial Supervision has no significant effect on Local Government performance, financial management accountability has a significant effect on Local Government performance, financial management transparency has a significant effect on Local Government performance.